PENERAPAN PENDEKATAN PEMECAHAN MASALAH DALAM MENINGKATKAN PEMAHAMAN KONSEP TERMOKIMIA PADA SISWA KELAS XI MADRASAH ALIYAH SITI MARIAM BANJARMASIN - Muhammad Kusasi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract: The classroom action research to increase students’ understanding through collaboration between lecturers of chemistry department and chemistry teachers in Siti Mariam’s Madrasah Aliyah Banjarmasin was established. This research intent to increase the eleventh grade students’ achievement of thermo chemistry concept. To increase students’ achievement, one of the learning strategies which can be used is problem solving. Therefore, the hypothesis came up on this research is by using problem solving method, students’ achievement of thermo chemistry shown by their ability to solve thermo chemistry problems can be improved. This study used classroom action research design with two cycles. The twenty eight of the eleventh grade students of Siti Mariam’s Madrasah Aliyah Banjarmasin on 2008/2009 school year were the subject of the research. By using achievement test and percentage as the technique of the data analysis was found that (1) students’ achievement on the initial observation was 30% (2) On the first cycle, students’ achievement increased from 30% to 65%, (3) Students’ achievement improved from 65% on the first cycle to 91% on the second cycle. Thus, it can be concluded that the implementation of the classroom action research on thermo chemistry through problem solving method was successful to increase students’ achievement.Key words: Problem solving approach, thermo chemistry concept.